2020
DOI: 10.33394/jollt.v8i1.2213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Team Product to Improve Students’ Creativity in Writing at SMPN 1 Jonggat

Abstract: This study investigated the effect of team product to improve students’ creativity in writing at the 8th-grade students of SMPN 1 Jonggat, Central Lombok in the academic year 2018/2019. The research was designed as quasi experiment research. The students were divided into the experimental group and control group. The experimental group was treated using the team product method while the control group was subjected to a conventional method. The data were analyzed using descriptive and inferential analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Third, the teacher divided the students into several groups. It is the same result shown by Prayati (2019) who conducts a study in which group works can help students to accomplish their writing easily. For students who lack academic ability in a group means that there are friends who can help, while the students' good academic ability can further enhance their capabilities.…”
Section: Discussionsupporting
confidence: 66%
“…Third, the teacher divided the students into several groups. It is the same result shown by Prayati (2019) who conducts a study in which group works can help students to accomplish their writing easily. For students who lack academic ability in a group means that there are friends who can help, while the students' good academic ability can further enhance their capabilities.…”
Section: Discussionsupporting
confidence: 66%
“…Based on it, creativity has indicators (1) expressing feeling/idea, (2) creating original work, and (3) solving the problem using the flexibility of thinking (Satria et al, 2022). Besides, the research has found the indicators of creativity as fluency (combining ideas), flexibility (thinking in many ways), originality (unique or new), and elaboration (expanding perspective) (Prayati, 2020;Soraya, 2016). Prayati (2020) has said that in writing for junior high school, students must present ideas concerning a story.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the research has found the indicators of creativity as fluency (combining ideas), flexibility (thinking in many ways), originality (unique or new), and elaboration (expanding perspective) (Prayati, 2020;Soraya, 2016). Prayati (2020) has said that in writing for junior high school, students must present ideas concerning a story. They must be creative in order to present a proper narration using sophisticated language.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speaking skills are also mastered by someone through listening activities who have recognized sounds and vocabulary. Reading skills must be possessed by everyone, because through reading a person acquires new vocabulary that helps enrich vocabulary so that it is more skillful (Prayati, 2020).…”
Section: Introductionmentioning
confidence: 99%